Profit Analysis and Marketing Strategy of Sagarurung Fish at MSMEs Suka Rasa in Talang Ubi District, Penukal Abab Lematang Ilir Regency - Sisvaberti Afriyatna; Innike Abdillah Fahmi; Billa Elviera (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
ABSTRACT This study aims to determine fresh Fish's advantages and marketing strategy in MSMES Suka Rasa Talang Ubi District, Penukal Abab Lematang Ilir Regency. The research method used is the case study method, for which purposive and quota sampling are used. Data collection methods used in this study are observation, interviews and documentation. Th,e results of the study found that the profitabilityof the Suka Rasa MSMEs were Rp. 8,486,329 / month and the IFAS and EFAS diagrams are in quadrant 4, the meeting between IFAS at point 0.85 and EFAS at point -0.47. So that is an alternative marketing strategy that can be done is to guarantee the quality of fresh fish products according to the criteria set by the company, and to increase product distribution, such as expanding the marketing reach by utilizing social media to promote products.